Kepemimpinan Transformasional sebagai Strategi untuk Meningkatkan Motivasi Kerja dalam Lingkungan Kerja Hybrid: Indonesia - Febriantina, Susan; Palupi, Amanda; Malikhah, Anindya Salsabila; Khatimah, Husnul; Maharani, Nadya Riska (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
The rapidly evolving work environment, particularly with the adoption of hybrid work settings, necessitates organizations to adapt swiftly and effectively. Transformational leadership, which centers on inspiration, motivation, and empowering employees, has demonstrated potential in fostering enhanced employee motivation and performance in these settings. Hybrid work environments, characterized by the combination of remote and in-office work, offer flexibility that can boost productivity and job satisfaction. However, these advantages are accompanied by challenges, such as maintaining employee psychological well-being, fostering effective communication, and building a sense of belonging. Addressing these issues is critical to minimizing negative impacts and optimizing the benefits of hybrid work. This study explores the role of transformational leadership in enhancing employee outcomes within hybrid environments by analyzing 12 relevant articles published between 2018 and 2023, sourced from Google Scholar using keywords such as